Electrolyte and lithium ion battery

By regulating the types and dosage of additives in the lithium-ion battery electrolyte, a SEI film structure dominated by inorganic components is formed, which solves the problem of insufficient conductivity and energy retention of lithium-ion batteries at low temperatures, and achieves low and high temperatures of lithium-ion batteries Improved performance balance.

CN119133596AActive Publication Date: 2024-12-13CHINA FAW CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411276264.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have insufficient charging and discharging capabilities at low temperatures, making it difficult to take into account both low temperature and high temperature performance, and the stability and conductivity of the electrolyte are difficult to maintain excellent at low temperatures.

Method used

By regulating the types and dosage of additives in the electrolyte, we ensure that the proportion of inorganic components is higher than that of organic components. We use a variety of lithium salts and organic solvents to form an SEI film structure dominated by inorganic components, and combine an appropriate amount of organic components to improve flexibility and stability.

Benefits of technology

The high conductivity and high energy retention rate of the electrolyte at low temperatures are achieved, while taking into account both room temperature and high temperature cycling performance, improving the low temperature and high temperature performance balance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040274270000071
    Figure BDA0005040274270000071
  • Figure BDA0005040274270000081
    Figure BDA0005040274270000081
  • Figure BDA0005040274270000082
    Figure BDA0005040274270000082
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to an electrolyte and a lithium ion battery. The electrolyte provided by the invention comprises a lithium salt, an organic solvent and an additive, the number of the types of additives satisfying a / b > = 1 / 2 accounts for 60% or more of the total number of the types of additives; the mass of the additive meeting the condition that a / b is greater than or equal to 1 / 2 accounts for 60-80% of the total mass of the additive; wherein a is the number of atoms except carbon, oxygen and hydrogen in each additive, and b is the number of carbon atoms in each additive. According to the electrolyte provided by the invention, by regulating and controlling the types and the use amounts of the additives and mutually matching all the components, the low-low-temperature DCR of the electrolyte and the high conductivity and the high energy retention rate at the low temperature can be realized, and the normal-temperature and high-temperature cycle performance can also be considered; when the composite material is applied to the lithium ion battery, the low-temperature performance and the normal-high-temperature performance of the lithium ion battery can be improved in a balanced manner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte and a lithium ion battery. Background Art

[0002] At present, electric vehicles have rapidly occupied the automobile market with advantages such as low energy consumption and zero carbon emissions, and are favored by the majority of users. With the development of technology, problems such as short driving range and long charging time have gradually been solved. At present, low-temperature performance is a pain point that restricts the application of electric vehicles in cold areas. Improving the charging and discharging capacity of batteries at low temperatures has also become the focus of technical research in the industry.

[0003] In lithium-ion batteries, the electrolyte has a significant impact on the low-temperature performance of the battery. The electrolyte is composed of solvents, lithium salts and additives. In order for the battery to have good low-temperature performance, the electrolyte needs to have the following properties: high lithium ion conductivity at low temperatures, good lithium ion conductivity of the SEI membrane, and fast charge transfer between the electrolyte and the electrode surface.

[0004] In the existing industry technology, low-temperature electrolytes are basically designed by combining low-melting-point solvents, high-dissociation lithium salts and low-impedance film-forming additives. Low-melting-point solvents are carboxylates such as EA and EP, lithium salts are often LiFSI as high-dissociation lithium salts, and film-forming additives are boron-containing additives such as LiBF4 and other additives containing S and P elements.

[0005] Carboxylic acid esters have better low-temperature performance, but poor electrode compatibility, especially poor reduction stability on the negative electrode surface. Due to the large amount of carboxylic acid esters used and the single solvent structure, the electrolyte stability is low, and its conductivity is limited by the amount of carboxylic acid esters used, it is difficult to achieve a balance between low-temperature performance and other properties. At this time, in order to take into account other room temperature and high temperature performance, the industry often increases the amount of high-temperature film-forming additives to improve high-temperature performance, but the low-temperature performance will suffer, and the problem of not being able to take into account both low-temperature performance and high-temperature performance often exists.

[0006] In view of this, this invention is proposed. Summary of the invention

[0007] The first object of the present invention is to provide an electrolyte having low low-temperature DCR, high conductivity and high energy retention rate at low temperatures, and excellent room temperature cycle performance and high temperature cycle performance.

[0008] A second object of the present invention is to provide a lithium ion battery having excellent low temperature performance and normal high temperature performance.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, the present invention provides an electrolyte comprising a lithium salt, an organic solvent and an additive;

[0011] The number of types of additives satisfying a / b≥1 / 2 accounts for more than 60% of the total number of types of additives; the mass of additives satisfying a / b≥1 / 2 accounts for 60% to 80% of the total mass of additives;

[0012] Wherein, a is the number of atoms other than carbon, oxygen and hydrogen in each additive, and b is the number of carbon atoms in each additive.

[0013] Further, the additive includes a first additive and a second additive;

[0014] The first additive includes at least one of vinyl sulfate, vinylene carbonate, tris(trimethylsilyl)phosphate, 1,3-propane sultone, methylene methanedisulfonate and fluoroethylene carbonate;

[0015] The second additive includes a lithium salt additive.

[0016] Furthermore, the number of types of the first additive is ≤4.

[0017] Furthermore, in the electrolyte, the mass percentage of the first additive is 1% to 2%.

[0018] Furthermore, the lithium salt additive includes at least one of lithium difluorophosphate, lithium difluorobisoxalatephosphate, lithium difluorooxalatoborate and lithium tetrafluoroborate.

[0019] Furthermore, in the electrolyte, the mass percentage of the second additive is 0.2% to 2%.

[0020] Further, the lithium salt includes lithium hexafluorophosphate and / or bis(fluorosulfonyl)imide lithium salt;

[0021] And / or, in the electrolyte, the content of the lithium salt is 10wt% to 20wt%.

[0022] Furthermore, the organic solvent includes at least one of cyclic carbonate, linear carbonate and carboxylate.

[0023] In a second aspect, the present invention further provides a lithium-ion battery comprising the electrolyte as described above.

[0024] Furthermore, the lithium-ion battery also includes a nickel-cobalt-manganese ternary positive electrode material, and the mass percentage of nickel in the nickel-cobalt-manganese ternary positive electrode material is ≥60%.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The electrolyte provided by the present invention can fully exert the synergistic effect of the components in the electrolyte by regulating the type and amount of additives in the electrolyte, without adding high-impedance high-temperature additives, and can achieve low low-temperature DCR, high conductivity and high energy retention rate of the electrolyte at low temperatures, while taking into account both normal temperature and high temperature cycle performance; the electrolyte of the present invention is used in lithium ion batteries, which is beneficial to the balanced improvement of the low-temperature performance and normal high temperature performance of the lithium ion batteries. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] An electrolyte and a lithium-ion battery according to an embodiment of the present invention are described in detail below.

[0029] In some embodiments of the present invention, an electrolyte is provided, including a lithium salt, an organic solvent and an additive;

[0030] The number of types of additives satisfying a / b≥1 / 2 accounts for more than 60% of the total number of types of additives; the mass of additives satisfying a / b≥1 / 2 accounts for 60% to 80% of the total mass of additives;

[0031] Wherein, a is the number of atoms other than carbon, oxygen and hydrogen in each additive, and b is the number of carbon atoms in each additive.

[0032] The electrolyte provided by the present invention is a low-temperature electrolyte. By regulating the type and amount of additives in the electrolyte, the synergistic effect of the components in the electrolyte is fully exerted, and there is no need to add high-impedance high-temperature additives. The electrolyte can achieve low low-temperature DCR, high conductivity and high energy retention rate at low temperatures, and can also take into account both normal temperature and high temperature cycle performance.

[0033] In some embodiments of the present invention, the number of types of additives satisfying a / b≥1 / 2 accounts for 60% to 75% of the total number of types of additives; typically but not limiting, for example, the number of types of additives satisfying a / b≥1 / 2 accounts for 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 75% of the total number of types of additives or a range consisting of any two of them.

[0034] In some embodiments of the present invention, typically but not limitatively, for example, the mass of the additive satisfying a / b≥1 / 2 accounts for 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80% or a range of any two thereof of the total mass of the additive.

[0035] The composition of SEI has a decisive influence on the performance. The ion conductivity of the inorganic component conforms to the Arrhenius relationship and has high low-temperature conductivity, while the viscosity of the organic component increases at low temperatures, the activation energy is high, and the ion transmission is slow. In addition, the inorganic component also has high stability, which is conducive to ensuring the stability and normal function of SEI at high temperatures. However, too much inorganic content will cause the SEI film to become brittle, and organic components need to be added for adjustment to enhance the flexibility of SEI. After reasonably adjusting the ratio of inorganic and organic components, high lithium ion permeability and mechanical stability of the SEI film can be achieved, thereby ensuring a balanced improvement in the low-temperature performance and normal high-temperature cycle performance of the battery.

[0036] The ratio of inorganic components to organic components has an important influence on the properties of SEI, and the composition of SEI is mainly determined by the type and amount of elements in the additive. a / b = the number of inorganic atoms in the additive other than C, O, and H / the number of C atoms is used as a parameter to measure the level of inorganic content of the additive, and it is considered that additives with a / b ≥ 1 / 2 are inorganic additives, such as DTD, etc., and additives with a / b < 1 / 2 are organic additives, such as VC. By regulating the type and quantity ratio of inorganic additives and organic additives in the electrolyte to meet the scope of the present invention, an SEI structure can be formed in which inorganic components are dominant and the inorganic components are uniformly dispersed in the organic component matrix. This structure can not only utilize the high lithium ion conductivity of the inorganic component to achieve high lithium ion permeability of the SEI membrane, but also can ensure that the SEI as a whole has sufficient mechanical stability with the help of the flexibility of the organic component, thereby ensuring a balanced improvement in the low temperature performance and normal high temperature cycle performance of the battery.

[0037] Inorganic additives and organic additives are defined by the present invention. For example, according to the definition, the inorganic atom in DTD is S, a in DTD is 1, b is 2, a / b=1 / 2, and therefore DTD belongs to inorganic additives.

[0038] In some embodiments of the present invention, the additive includes a first additive and a second additive;

[0039] The first additive includes at least one of vinyl sulfate (DTD), vinylene carbonate (VC), tris(trimethylsilyl) phosphate (TMSP), 1,3-propane sultone (PS), methylene methane disulfonate (MMDS), and fluoroethylene carbonate (FEC);

[0040] The second additive includes a lithium salt additive.

[0041] In some embodiments of the present invention, the number of types of the first additive is ≤4; typically but not limiting, for example, the number of types of the first additive may be 1, 2, 3 or 4; preferably, the number of types of the first additive is 3.

[0042] In some embodiments of the present invention, in the electrolyte, the mass percentage of the first additive is 1% to 2%; typically but not limitatively, for example, in the electrolyte, the mass percentage of the first additive can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or a range consisting of any two of them.

[0043] In the electrolyte of the present invention, if the content of the first additive is too high, the battery impedance will increase and the low-temperature discharge capacity will be weakened; if the content of the first additive is too low, the SEI will be difficult to be fully repaired during the cycle, and the cycle performance will deteriorate.

[0044] In some embodiments of the present invention, in the electrolyte, the mass percentage of each first additive is ≥ 0.1%.

[0045] In the electrolyte, if the mass percentage of each first additive is low, it will have an adverse effect on the cycle performance of the battery.

[0046] In some specific embodiments of the present invention, the first additive includes DTD, VC and TMSP; and in the electrolyte, the mass percentages of DTD, VC and TMSP are all ≥ 0.1%; preferably, the mass ratio of DTD, VC and TMSP is (5-10): (1-5): (1-5).

[0047] In some embodiments of the present invention, the lithium salt additive includes at least one of lithium difluorophosphate (LiPO2F2), lithium difluorodioxalatophosphate (LiODFP), lithium difluorooxalatoborate (LiODFB) and lithium tetrafluoroborate (LiBF4).

[0048] In some embodiments of the present invention, in the electrolyte, the mass percentage of the second additive is 0.2% to 2%; typically but not limitatively, for example, in the electrolyte, the mass percentage of the second additive can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2% or a range of any two thereof.

[0049] In some embodiments of the present invention, the lithium salt includes lithium hexafluorophosphate (LiPF6) and / or lithium bis(fluorosulfonyl)imide (LiFSI).

[0050] In some embodiments of the present invention, the content of lithium salt in the electrolyte is 10wt% to 20wt%; typically but not limitatively, for example, the content of lithium salt in the electrolyte can be 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt% or a range consisting of any two of them.

[0051] In some embodiments of the present invention, the organic solvent includes at least one of a cyclic carbonate, a linear carbonate, and a carboxylic acid ester.

[0052] In some specific embodiments of the present invention, the organic solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0053] In some embodiments of the present invention, a method for preparing the above electrolyte is also provided, comprising the following steps:

[0054] After the lithium salt, the organic solvent and the additive are evenly mixed, an electrolyte is obtained.

[0055] In some embodiments of the present invention, a lithium-ion battery is provided, comprising the above-mentioned electrolyte.

[0056] The use of the electrolyte of the present invention in lithium-ion batteries is beneficial to simultaneously and balancedly improve the low-temperature performance and normal high-temperature performance of the lithium-ion batteries.

[0057] In some embodiments of the present invention, the lithium-ion battery further comprises a nickel-cobalt-manganese (NCM) ternary positive electrode material, and the mass percentage of nickel in the nickel-cobalt-manganese ternary positive electrode material is ≥ 60%.

[0058] In some embodiments of the present invention, the lithium-ion battery further comprises a negative electrode material, and the negative electrode material includes but is not limited to graphite.

[0059] In some embodiments of the present invention, the upper limit of the operating voltage of the lithium-ion battery is not higher than 4.4V.

[0060] Examples 1 to 7

[0061] The method for preparing the electrolyte provided in this embodiment comprises the following steps:

[0062] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 2:4.5:3.5 to form an organic solvent; then lithium salt and additives were added and mixed evenly to obtain an electrolyte; wherein the lithium salt was lithium hexafluorophosphate, and the content of the lithium salt in the electrolyte was 12wt%; the composition of the additives and the content of each additive component in the electrolyte are shown in Table 1.

[0063] In Table 1, the content of each component is the percentage of the mass of each component to the total mass of the electrolyte.

[0064] Table 1

[0065]

[0066]

[0067] Comparative Examples 1 to 6

[0068] The preparation method of the electrolyte provided in this comparative example comprises the following steps:

[0069] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 2:4.5:3.5 to form an organic solvent; then lithium salt and additives were added and mixed evenly to obtain an electrolyte; wherein the lithium salt was lithium hexafluorophosphate, and the content of the lithium salt in the electrolyte was 12wt%; the composition of the additives and the content of each additive component in the electrolyte are shown in Table 2.

[0070] In Table 2, the content of each component is the percentage of the mass of each component to the total mass of the electrolyte.

[0071] Table 2

[0072]

[0073]

[0074] Test example

[0075] Lithium ion batteries were assembled using the electrolytes of Examples 1 to 7 and Comparative Examples 1 to 6, and the electrochemical performance of each battery was tested. The results are shown in Table 3.

[0076] A method for preparing a lithium-ion battery comprises the following steps:

[0077] The positive electrode active material (ternary NCM, LiNi 0.6 Co 0.2 Mn 0.2O2), polyvinylidene fluoride as a binder and Super P as a conductive agent are mixed in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes uniform and transparent to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil; the aluminum foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet;

[0078] Artificial graphite is used as the negative electrode active material, Super P is used as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as the thickener, and styrene-butadiene rubber (SBR) is used as the binder, and the mixture is mixed in a mass ratio of 96:1:1:2, and deionized water is added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode sheet;

[0079] A polypropylene film (PP) with a thickness of 12 μm was used as an isolation film, and the positive electrode sheet, isolation film, and negative electrode sheet prepared above were stacked in sequence, so that the isolation film was located between the positive and negative electrodes to play an isolating role; then they were wrapped with an aluminum-plastic film, transferred to a vacuum oven at 120°C for drying, and sealed after injecting 3.0 g / Ah of electrolyte, and the electrolyte was formed to finally prepare a soft-pack battery (i.e., a lithium-ion battery) with a capacity of 1 Ah.

[0080] The electrochemical performance test method is as follows:

[0081] Secondary battery cycle test: In an oven at a specified temperature (room temperature 25°C or high temperature 45°C), cyclic charge and discharge are performed at a current of 1C within a specified potential range, and the discharge capacity of each cycle is recorded. The test is terminated when the battery capacity reaches 80% of the first cycle capacity.

[0082] Secondary battery DC resistance (DCR) test: At a specified temperature, when the battery is discharged to 50% SOC (state of charge, reflecting the remaining capacity of the battery) at a current of 1C, the current is increased to 4C and maintained for 30s. The difference between the updated stable voltage and the original platform voltage is detected. The ratio of its value to the 4C current value is the DC resistance of the battery. The DCR test result after the battery is fully charged for the first time is the initial DCR of the battery.

[0083] Secondary battery low temperature discharge capacity retention rate test: After the secondary battery is fully charged, it is placed in a -20°C constant temperature box. After sufficient cooling, it is discharged at a 1C rate to the cut-off voltage, and its capacity is compared with the percentage of the initial discharge capacity.

[0084] The battery charge and discharge cut-off voltage is: 2.8~4.4V.

[0085] Table 3

[0086]

[0087]

[0088] As can be seen from Table 3, by comparing Example 1, Example 2 and Comparative Example 1, it can be seen that the number of additive types with a large proportion of inorganic components has an important influence on the low-temperature performance. The higher the proportion of such additive types, the better the low-temperature performance. However, too much inorganic component will cause SEI to become brittle, and the corresponding cycle performance will be adversely affected.

[0089] From the comparison of Example 1, Example 3, Example 4, Comparative Example 2 and Comparative Example 3, it can be seen that in addition to the type of additives, the content of the additives will also affect the level of inorganic components in SEI. When the content of the additive with a large proportion of inorganic components is high, the low-temperature performance of the battery is improved. When the content of the additive with a large proportion of inorganic components is beyond the limit range of the present invention (≤60% or ≥80%), the low-temperature performance and normal high-temperature cycle performance cannot be taken into account at the same time.

[0090] From the comparison among Example 1, Example 5, Example 6, Comparative Example 4 and Comparative Example 5, it can be seen that the total amount of the first additive also needs to be controlled within a reasonable range; too high a content of the first additive will lead to an increase in battery impedance and a weakening of low-temperature discharge capability, while too low a content of the first additive will lead to difficulty in fully repairing the SEI during the cycle, resulting in deterioration of the cycle performance.

[0091] Comparison of Example 1, Example 7 and Comparative Example 6 shows that using three first additives can achieve better results, and reducing the types of first additives will affect the cycle performance of the battery.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrolyte, It is characterized in that Including lithium salts, organic solvents and additives; The number of types of additives satisfying a / b≥1 / 2 accounts for more than 60% of the total number of types of additives; the mass of additives satisfying a / b≥1 / 2 accounts for 60% to 80% of the total mass of additives; Wherein, a is the number of atoms other than carbon, oxygen and hydrogen in each additive, and b is the number of carbon atoms in each additive.

2. The electrolyte according to claim 1, It is characterized in that The additives include a first additive and a second additive; The first additive includes at least one of vinyl sulfate, vinylene carbonate, tris(trimethylsilyl)phosphate, 1,3-propane sultone, methylene methanedisulfonate and fluoroethylene carbonate; The second additive includes a lithium salt additive.

3. The electrolyte according to claim 2, It is characterized in that The number of types of the first additive is ≤4.

4. The electrolyte according to claim 3, It is characterized in that In the electrolyte, the mass percentage of the first additive is 1% to 2%.

5. The electrolyte according to claim 4, It is characterized in that The lithium salt additive includes at least one of lithium difluorophosphate, lithium difluorobisoxalatephosphate, lithium difluorooxalatoborate and lithium tetrafluoroborate.

6. The electrolyte according to claim 5, It is characterized in that In the electrolyte, the mass percentage of the second additive is 0.2% to 2%.

7. The electrolyte according to claim 6, It is characterized in that The lithium salt includes lithium hexafluorophosphate and / or bis(fluorosulfonyl)imide lithium salt; And / or, in the electrolyte, the content of the lithium salt is 10wt% to 20wt%.

8. The electrolyte according to claim 6, It is characterized in that The organic solvent includes at least one of cyclic carbonate, linear carbonate and carboxylic acid ester.

9. A lithium ion battery, It is characterized in that The electrolyte comprises the electrolyte described in any one of claims 1 to 8.

10. The lithium ion battery according to claim 9, It is characterized in that The lithium-ion battery also includes a nickel-cobalt-manganese ternary positive electrode material, and the mass percentage of nickel in the nickel-cobalt-manganese ternary positive electrode material is ≥60%.

Citation Information

Patent Citations

  • Ternary positive electrode material lithium ion battery electrolyte

    CN107069090A

  • Long-cycle lithium ion electrolyte and battery

    CN109659609A

  • High-nickel ternary lithium ion battery electrolyte and ternary lithium ion battery

    CN112216862A

  • High-low temperature lithium ion battery electrolyte and lithium ion battery

    CN112310473A

  • Electrolyte with both low-temperature quick charge performance and high-temperature performance and preparation method and application thereof

    CN112652816A